2010
DOI: 10.1177/0897190009356549
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced QTc-Interval Prolongation in the Intensive Care Unit: Incidence and Predictors

Abstract: There is a paucity of information regarding QTc prolongation in critically ill patients. A prospective observational study was conducted to assess the incidence and predictors of QTc prolongation associated with medications in intensive care unit (ICU) patients. Consecutive adult patients prescribed prespecified QTc-prolonging medications were assessed for development of the combined incidence of QTc >500 ms at anytime and QTc increase >60 ms above baseline. Over 3 months, 200 consecutive patients (63 ± 18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
2
13
0
1
Order By: Relevance
“…Thus, it is most likely that the QTc was overlooked or ignored. This maybe particularly dangerous during admissions for acute illnesses and particularly in intensive care settings where there are frequent transitions of care and rapidly changing clinical conditions . Our findings are particularly resonant with those of Tisdale et al .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, it is most likely that the QTc was overlooked or ignored. This maybe particularly dangerous during admissions for acute illnesses and particularly in intensive care settings where there are frequent transitions of care and rapidly changing clinical conditions . Our findings are particularly resonant with those of Tisdale et al .…”
Section: Discussionsupporting
confidence: 67%
“…Our report corroborates previous studies that medications known to prolong QTc are commonly administered in combination. This is particularly true among inpatients in the acute inpatient setting . Inpatients not infrequently received two or more medications known to prolong QTc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in ICU populations found prolongation of QTc above 500 ms in 13%–40% of patients, partially caused by medication 7 11 12. Prolongation of QTc in ICU is associated with longer lengths of hospitalisation and increased mortality 13.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 Corrected QT (QTc) prolongation is defined as a QTc interval more than 440 milliseconds in men and 460 milliseconds in women, with the risk of arrhythmias increasing when values are 500 milliseconds or more. 21,22 Corrected QT (QTc) prolongation is defined as a QTc interval more than 440 milliseconds in men and 460 milliseconds in women, with the risk of arrhythmias increasing when values are 500 milliseconds or more.…”
Section: Corrected Qt Prolongationmentioning
confidence: 99%